Giants with feet of clay? An inquiry into user payment patterns for subscription video-on-demand services - Ignacio Redondo; Diana Serrano (Administrative Sciences, 2023)
Subscription video-on-demand platforms such as Netflix and HBO Max are being increasingly challenged by the widespread practice of sharing accounts with individuals outside the household. Platforms face a massive loss of revenue due to the opportunistic behavior of many users who enjoy content without paying anything or paying only a part of the required subscription fees. This study explores which factors influence platform users to pay all, part, or none of the subscription fees. Using a cross-sectional survey from Spain, various demographic, attitudinal, and behavioral factors were identified as predictors of the patterns of full, partial, and non-payment. The findings may help platform managers tailor some interventions to monetize a larger number of actual users by deterring the opportunistic payment patterns without discouraging the full payment pattern.
Keywords: 350; account sharing; consumer behavior; digital piracy; film business